Human seminal plasma stimulates the migration of CD11c+ mononuclear phagocytes to the apical side of the colonic epithelium without altering the junctional complexes in an ex vivo human intestinal model - Baratella, Marco; Iannone, Valeria; Cavarelli, Mariangela; Foglieni, Chiara; Viganò, Paola; Moog, Christiane; Elmore, Ugo; Nozza, Silvia; Alfano, Massimo; Salonia, Andrea; Dispinseri, Stefania; Scarlatti, Gabriella (Frontiers in Immunology, 2023)
Human immunodeficiency virus type 1 (HIV) transmission mostly occurs through the genital and intestinal mucosae. Although HIV-1 transmission has been extensively investigated, gaps remain in understanding the initial steps of HIV entry through the colonic mucosa. We previously showed that HIV can selectively trigger mononuclear phagocytes (MNP) to migrate within colonic epithelial cells to sample virions. Mucosal exposure to human seminal plasma (HSP), rich in pro- and anti-inflammatory cytokines, chemokines and growth factors, may as well induce alterations of the colonic mucosa and recruit immune cells, hence, affecting pathogen sampling and transmission. Here, we studied the role of HSP on the paracellular intestinal permeability by analyzing the distribution of two proteins known to play a key role in controlling the intestinal barrier integrity, namely the tight junctions-associated junctional adhesion molecule (JAM-A) and the adherents junction associated protein E-cadherin (E-CAD), by immunofluorescence and confocal microscopy. Also, we evaluated if HSP promotes the recruitment of MNP cells, specifically, the CD11c and CD64 positive MNPs, to the apical side of the human colonic mucosa. At this scope, HSP of HIV-infected and uninfected individuals with known fertility status was tested for cytokines, chemokines and growth factors concentration and used in an ex vivo polarized colonic tissue culture system to mimic as closely as possible the physiological process. HSP showed statistically significant differences in cytokines and chemokines concentrations between the three groups of donors, i.e. HIV infected, or uninfected fertile or randomly identified. Nevertheless, we showed that in the ex vivo tissue culture HSP in general, neither affected the morphological structure of the colonic mucosa nor modulated the paracellular intestinal permeability. Interestingly, CD11c+ MNP cells migrated to the apical surface of the colonic epithelium regardless, if incubated with HIV-infected or -uninfected HSPs, while CD64+ MNP cells, did not change their distribution within the colonic mucosa. In conclusion, even if HSP did not perturb the integrity of the human colonic mucosa, it affected the migration of a specific subset of MNPs that express CD11c towards the apical side of the colonic mucosa, which in turn may be involved in pathogen sampling.